2000
DOI: 10.1177/00220345000790071101
|View full text |Cite
|
Sign up to set email alerts
|

Proviral HIV-1 DNA in Gingival Crevicular Fluid of HIV-1-infected Patients in Various Stages of HIV Disease

Abstract: The oral cavity is rarely reported to be a site of human immunodeficiency virus (HIV) transmission, despite detectable virus in saliva and relatively frequent prevalence of periodontal disease in HIV-infected persons yielding increased excretion of mononuclear-cell-enriched gingival fluid. To search for possible sources of HIV in saliva, and using the polymerase chain-reaction technique, we sought the presence and shedding patterns of proviral HIV-1 DNA in gingival crevicular fluid in a group of patients previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
51
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 46 publications
8
51
0
Order By: Relevance
“…Consistently across studies, salivary HIV-1 is positively associated with plasma HIV-1 viral load with Pearson's correlation coefficients ranging from 0.21 to 0.51 4 7 11. Other factors commonly associated with plasma HIV levels, such as blood CD4 count, antiretroviral therapy (ART) and stage of disease, are inconsistently associated with oral shedding of HIV-1 9 13 14.…”
Section: Introductionmentioning
confidence: 71%
“…Consistently across studies, salivary HIV-1 is positively associated with plasma HIV-1 viral load with Pearson's correlation coefficients ranging from 0.21 to 0.51 4 7 11. Other factors commonly associated with plasma HIV levels, such as blood CD4 count, antiretroviral therapy (ART) and stage of disease, are inconsistently associated with oral shedding of HIV-1 9 13 14.…”
Section: Introductionmentioning
confidence: 71%
“…Moreover, it was recently demonstrated that P. gingivalis could up-regulate CCR5 in oral keratinocytes (31) and thus facilitate the subsequent infection of HIV into permissive cells such as macrophages in a CCR5-dependent manner (32). In addition, there was a significant correlation between the clinical stage of periodontitis and the HIV-1 proviral DNA load in gingival crevicular fluid as well as the HIV-1 RNA viral load in plasma (33,34) and saliva (34). More P. gingivalis organisms were found in the HIV-1-positive individuals than in the otherwise healthy controls (35,36).…”
Section: Reactivation Of Latent Hiv-1 Infection By the Periodontopathmentioning
confidence: 99%
“…3,15,48-58 These include technologies used for high-throughput tests conducted in clinical laboratories, as well as rapid, single-sample tests for POC or home-testing devices. As is seen for other infectious diseases, salivary antibody diagnostics for HIV are as effective as blood-based diagnostics.…”
Section: Major Viral Infectionsmentioning
confidence: 99%